Maqashid Syariah Sebagai Landasan Pengembangan Produk Perbankan Syariah - Mifta Hasda; Mohd Winario; Rahmawati Rahmawati (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
The development of the Islamic banking industry in Indonesia is currently dominated by a formal sharia compliance approach on the legality of contracts, but has not been fully and systematically integrated with the substantive values of maqashid sharia. This study aims to identify the types and characteristics of Islamic banking products, examine the principles of maqashid sharia as a foundation for product development, and analyze the implementation of maqashid sharia within the operational schemes of Islamic banking products. Utilizing a qualitative approach with a library research method and content analysis technique, data were gathered from various academic literatures, regulations, and authoritative fatwas. The results indicate that Islamic banking products—categorized into funding, financing, and financial services—have implemented the five core pillars of preservation (al-kulliyat al-khamsah). This actualization is reflected in: (1) hifdz al-din through the elimination of riba, gharar, maysir, and the integration of ZISWAF; (2) hifdz al-nafs through the mutualism principle in contracts and sharia insurance risk mitigation; (3) hifdz al-’aql through product information disclosure and financial education; (4) hifdz al-nasl through the provision of future family financial planning products; and (5) hifdz al-mal through optimizing intermediation functions in halal real sectors and accountable risk management. This study concludes that maqashid sharia parameters must be established as primary indicators for product achievement and evaluation to realize sustainable welfare (maslahah) and distributive justice substantively for society.